Lo scrittore e lo storico. Percorsi di una lettera di Italo Calvino a Delio Cantimori sul Barone rampante - Parodi, Jacopo (L’ospite ingrato, 2024)
Starting from a letter by Italo Calvino to Delio Cantimori, this contribution aims to read the relationship between historical truth and fictional truth, trying to understand the thread that runs between Il Barone rampante and Cantimori’s historiography, in particular that which focuses on the Italian Jacobins. What does it mean that Calvino’s novel has a close connection with Cantimori’s Utopisti? In other words, was Baron Cosimo born from the reading of a particular historiography, with a narrative scope, such as that of Delio Cantimori or, to give another example, of Franco Venturi? What is the feeling of history and history as tragedy that inhabits and expresses a fantastic novel such as Calvino’s?